Students’ knowledge and attitudes toward basic life support - Mysara Alfakey; Ahmed Alkarani (International Journal of Evaluation and Research in Education (IJERE), 2021)
Students spend a significant proportion of their day in colleges and healthcare facilities where they might experience medical emergencies, or unexpected accidents, that occur in these places. Nursing students are expected to play a key role in performing basic life support. This study is to evaluate knowledge, attitudes and training status with regard to basic life support (BLS). An online cross-sectional survey was conducted in Taif University, Saudi Arabia. 170 students agreed to fill out a questionnaire. The questions used in the questionnaire were prepared according to 2015 AHA guidelines. The majority of subjects (52.9%) reported that they had attended a BLS course. The mean age of the study population was 21.64 years. Previous CPR training had a significant effect on the correct responses (P <0.01). This study found significant differences between the students observed: (58.3%) of students with previous BLS training felt capable of providing CPR to their fellow college students, compared to (42.7%) in the group without previous training (P =0.01). Importantly, over all subjects the attitude to learning on a BLS training course was positive. Inconclusions this study corroborates previous reports that the knowledge, skills and attitudes of trained students are better than those of untrained students.